Effects of dietary lysine on broiler performance and carcass yield - meta-analysis - AS Mendes; I Api; L Silva; RTL Silva; L Sausen; LFG Menezes; GM Morello; EH Carvalho (Brazilian Journal of Poultry Science, 2014)
There has been a great evolution and improvement in the nutrition of poultry and lysine has been used the reference amino acid to increase animal protein deposition. Therefore, a meta-analysis was performed with the objective of studying the effect of different dietary lysine levels on the performance and carcass yield of broiler chickens. In total, 21 studies published in Brazil since 1999 were included. Bird performance considered daily weight gain (178 observations) and feed conversion ratio (188 observations) results. Carcass quality was evaluated relative to carcass yield (24 observations), abdominal fat (24 observations) and breast meat yield (30 observations). Data were checked for normality and were submitted to analysis of variance. Weight gain and carcass yield increased with the addition of 1.05% of lysine to the diet, whereas feed conversion ratio and abdominal fat were reduced as dietary lysine concentration increased. The results, therefore, indicate that lysine is essential in bird nutrition and significantly affects bird performance and carcass yield.